Outcomes and predictors of mortality in patients with blunt chest trauma admitted to the intensive care unit: a retrospective study - Hefny, Ashraf F.; Elkamhawy, Ashraf A.; Fathi, Sherif A.; Zoubeidi, Taoufik; Alshamsi, Fayez (Frontiers in Medicine, 2025)
BackgroundBlunt chest trauma (BCT) accounts for 25% of trauma-related deaths. we aimed to explore the outcomes and predictors of mortality in patients with BCT admitted to a general intensive care unit (ICU).MethodsAll patients with multiple traumas and BCT who were admitted to the ICU between December 2014 and January 2017 were retrospectively studied. Details on their injuries, demographic characteristics, Glasgow Coma Scale (GCS) score, injury severity score, management, and mortality during ICU admission were retrieved from the hospital trauma registry.ResultsNinety-two patients were admitted to the ICU. Most cases of BCTs were caused by motor vehicle accidents (75%). Ten patients died (overall mortality: 10.9%). Simple logistic regression analysis identified GCS score, invasive mechanical ventilation, and acute physiology and chronic health evaluation II (APACHE II) score as significant predictors of mortality. Multivariate logistic regression analysis revealed that the APACHE II score was the best predictor of mortality. A one-unit increase in the APACHE II score corresponded to a 17% increase in the odds of death, and an APACHE II score of ≥15 had a sensitivity and specificity of 90 and 81.7%, respectively, in predicting ICU mortality.DiscussionBCTs were common among patients with polytrauma, and together with concomitant injuries leads to significant ICU resource utilization and worse outcomes.ConclusionThe APACHE II score, GCS score, and mechanical ventilation were significantly associated with mortality among patients with BCT admitted to the ICU. These factors may be considered for early ICU triage.